Genesis of Titaniferous Magnetites and Associated Rocks of the Lake Sanford District, New York - J. L. Gillson (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1956)
The big mass of anorthosite in the Lake Sanford district and the bodies of titaniferous magnetite that occur in a small area near the south margin of the mass have been described repeatedly, and the puzzling problems of the genesis of the rocks and ores have stimulated the deductive reasoning of geologists for a hundred years. Some of these men have taken a leading part in describing the anorthosite rock and forming hypotheses concerning its origin; some have contributed most to the study of the ore deposits; and some have made classical Studies introducing a basic approach to the problems of the anorthosite rock and genesis of the titaniferous magnetites. Much of the writing on the problems of rock and ore genesis has been based on physical-chemical reasoning rather than on field and microscope observations of the rocks and ores. Most of these geologists conclude that the anorthosite was formed by true magmatic crystallization, involving previous settling or squeezing out of ferromagnesian minerals from the parent magma. The associated gabbro is a separate segregation or later intrusion, and the lighter colored and finer grained facies of the anorthosite is either a chilled border zone of the anorthosite or the result of granulation by crushing of the coarse, dark blue rock of the main mass. This blue rock, called the Marcy type, is named after the highest peak in the range. The finer grained and lighter colored rock is called the Whiteface, after another mountain appropriately named for a cliff colored by this facies of the anorthosite.